Growth and survival of milkfish (Chanos chanos), tiger prawns (Panaeus monodon), and oysters (Crassostrea sp.) in integrated multi-trophic aquaculture (IMTA) system with varying stocking densities - Andika, Maulana; Muliani, Muliani; Khalil, Munawar (Universitas Malikussaleh, 2024)
Integrated Multitrophic Aquaculture System (IMTA) is a sustainable approach to aquaculture, utilizing ecosystem dynamics by integrating various species. This study examined the growth and survival of milkfish (Chanos chanos), tiger shrimp (Penaeus monodon), and oysters (Crassostrea spp.) in IMTA systems with different stocking densities. A 30-day experiment using a nonfactorial-completely randomized design with four treatments and three replications was conducted. The results showed that the implementation of IMTA had no significant impact on the survival rate of milkfish, tiger prawns or oysters in all treatments. However, important variations in growth parameters were observed. Milkfish and tiger prawns showed the highest weight and length gain in treatment B, followed by treatments A, C, and D. Similarly, oysters showed optimal growth in treatment B, followed by A, C, and D, based on weight gain, length, width, and shell thickness. Throughout the study, the physicochemical parameters of the water remained within acceptable ranges, thus supporting ideal growth conditions for the cultured species. These findings underscore the potential of IMTA to increase aquaculture productivity while upholding the principles of environmental sustainability. By optimizing stocking density and encouraging species diversity, IMTA presents a promising avenue for advancing integrated aquaculture practices, in line with the FAO's blue economy concept and ecosystem approach to aquaculture. Future research should concentrate on refining the IMTA system and evaluating its long-term ecological and economic consequences.